Pengukuran Kinerja Komitmen Organisasi Pada Kinerja Manajerial Dengan Financial Distress Sebagai Pemoderasi - Uum Helmina Chaerunnisak; Andri Wskita Adji (UMSurabaya Publishing, 2020)
Business competition in this day and age is considered to be very tight, increasing the efforts of UMKM to improve managerial performance. Starting from the improvement from the management side to thr improvement of service to consumers. Long term goal: study the effect of the performance measurement system, organizational commitment on managerial performance with financial distress as a moderating variable in UMKM Yogyakarta. The method used to achieve the goal is to distribute questionnaire are processed using to the SEM-PLS methods and analyzed. The data that can be obtained from 88% of the total data are 88 respondents. The results of this study state about positive performance measurements of managerial performance. Organizational commitment does not lead to managerial performance. Financial distress do not affect managerial performance. Then, performance measurement positively influences managerial performance with financial distress as predictor of moderation. And, finally organizational commitment to managerial performance with financial distress as homologous moderator or potential moderation. Keywords : Performance Measurement, Organizational Commitment, Financial Distress, Managerial Performance